Affirmation of Cultural Heritage Digital Promotion within Smart Destination Concept (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
The paper explores the perspectives of implementing digital, online promotion within the concept of smart destination development, aiming for the competitiveness that innovative tools and systems enable. Built heritage in developed tourism destinations presents an attractive resource, and its presentation through digital technology impacts culture's perception. With the development of new technologies and the adoption new digital and tourism trends, e-tourism cultural heritage promotion represents a significant challenge for destinations. Research design includes the identification of cultural heritage in tourism destinations followed by the longitudinal study, the research of progress in technology implementation, and an analysis of key tools for digital promotion. Several aspects are explored: online promotion, digitalization of heritage, and WiFi coverage for social networks' real-time streaming. Qualitative and quantitative methods aim to contribute new knowledge about the important use of online digital tools. The paper points to how the advantages and potentials of developing a smart culture in a destination, recognised as a strategic policy of development, are implemented in the digital marketing of heritage sites.